OPTIMIZATION OF THE PRIMUM REMEDIUM PRINCIPLE IN ENVIRONMENTAL CRIMES - simanjuntak, Ega Sang Bintang (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2024)
Environmental crime is still one of the problems faced, and there is a need for sanctions to provide a deterrent effect for the perpetrators. In Law Number 32 of 2009, one enforcement of environmental criminal law is the principle of premium medium, which states that criminal law is the primary tool in law enforcement. However, in Law Number 6 of 2023 concerning the Stipulation of Government Regulation instead of Law Number 2 of 2022 concerning Job Creation, there are changes in the punishment system that make punishment the last legal remedy (Ultimum Remedium) even though the determination of the punishment system has a crucial/critical position to reduce the high level of crime or environmental violations, This has also weakened the power of environmental law and is also contrary to the constitution which adheres to the concept of Green Constitution. This research aims to identify and describe how to strengthen the principle of Premium Remedium in environmental law regulation. The research method used is normative juridical, describing the synchronization of legislation that applies in a particular field, whether it contradicts or not between one another. There are still many problems regarding environmental law regulation, especially in the punishment system, the normative framework that provides lighter sanctions to environmental criminals; this is contrary to the PPLH Law, which makes punishment the primary legal remedy.